Scafolding as An Alternative Way to Develop The Ability of Critical Thinking in The Life of Digital Era - Kintoko Kintoko; S. B. Waluya; Iwan Junaedi; Nuriana Rachmani Dewi (International Conference on Science, Education, and Technology, 2021)
Critical thinking skills are one of the must-have abilities students in the 21st century must have. Critical thinking is one of the high-level thinking according to (Zembal-Saul et al., 2002) high order thinking is a combination of critical thinking, creative thinking, and basic knowledge thinking. Critical thinking means putting yourself in an active quest to understand what is going on by using reasoning procedures, evaluating evidence, and carefully weighing the thought process itself. In fact, students still have difficulty thinking critically of mathematics. This paper examines scaffolding as one of the efforts to improve critical thinking skills. Scaffolding can be given to students in the form of modeling certain behaviors (modeling of desired behaviors), presenting explanations (offering explanations), inviting student participation (inviting student participation), verifying and clarifying student understandings, and inviting students to contribute clues. In principle scaffolding is given then the provision of scaffolding is reduced and ultimately eliminated after the student has gained understanding.